In-situ high-pressure x-ray diffraction study of zinc ferrite nanoparticles - Ferrari, Sergio (2016)
We have studied the high-pressure structural behavior of zinc ferrite (ZnFe2O4) nanoparticles by powder X-ray diffraction measurements up to 47 GPa. We found that the cubic spinel structure of ZnFe2O4 remains up to 33 GPa and a phase transition is induced beyond this pressure. The high-pressure phase is indexed to an orthorhombic CaMn2O4-type structure. Upon decompression the low- and high-pressure phases coexist. The compressibility of both structures was also investigated. We have observed that the lattice parameters of the high-pressure phase behave anisotropically upon compression. Further, we predict possible phase transition around 55 GPa. For comparison, we also studied the compression behavior of magnetite (Fe3O4) nanoparticles by X-ray diffraction up to 23 GPa. Spinel-type ZnFe2O4 and Fe3O4 nanoparticles have a bulk modulus of 172 (20) GPa and 152 (9) GPa, respectively. This indicates that in both cases the nanoparticles do not undergo a Hall-Petch strengthening.